Children with PIMD in interaction with peers with PIMD or siblings. (29th September 2015) - Nijs, S.; Vlaskamp, C.; Maes, B.
Abstract: Background: The complex disabilities of children with profound intellectual and multiple disabilities (PIMD) impede their presentation of peer directed behaviours. Interactions with typically developing peers have been observed to be more frequent than those with peers with PIMD. The typically developing peers with whom people with PIMD have frequent contact are their siblings. In this study, the amount of peer directed behaviours was compared between an interaction with a sibling and an interaction with a peer with PIMD. In addition, the attention directing strategies of the siblings, and how these affect the presentation of peer directed behaviours, were examined. Method: Thirteen children and young people with PIMD, who had a typically developing sibling, were identified. For each of these thirteen children, a peer with PIMD and a sibling were selected. The child with PIMD was observed together with a peer with PIMD and together with a sibling. In both conditions, video observations were conducted. A coding scheme for the peer directed behaviours of the children and young people with PIMD and a coding scheme for the attention directing behaviours of the siblings were used. Descriptive, comparative and sequential analyses were conducted. Results: Significantly, more peer directed behaviours of the children with PIMD were observed in the condition with the sibling (30.76%) compared with that of the condition with the peer with PIMD (13.73%). The siblings presented attention directing behaviours in 30% of the time; the most frequently used was nonverbal behaviour. When the siblings presented a combination of verbal and nonverbal attention directing behaviours, they elicited multiple peer directed behaviours in the children and young people with PIMD. Conclusions: Persons with PIMD interact more with their siblings compared with their peers with PIMD. Interacting with siblings may probably be more motivating and encouraging. Presenting a combination of verbal and nonverbal behaviours attracts more attention of the persons with PIMD.